Allergic rhinitis and risk of systemic lupus erythematosus: A systematic review and meta-analysis - Wasit Wongtrakul (2020)
© 2020 Asia Pacific League of Associations for Rheumatology and John Wiley & Sons Australia, Ltd Objective: The current study was conducted to comprehensively investigate whether patients with allergic rhinitis (AR) are at a higher risk of incident systemic lupus erythematosus (SLE) compared with individuals without AR by using systematic review and meta-analysis techniques to combine data from all available studies. Methodology: Systemic literature review was performed using EMBASE and MEDLINE databases up to March 2020. Eligible studies could be either case-control or cohort studies. Cohort studies had to evaluate whether patients with AR have a higher risk of incident SLE than comparators. Relative risk (RR) with associated 95% confidence intervals (CI) comparing the incidence of SLE between participants with and without AR had to be provided. Eligible case-control studies had to provide odds ratio (OR) with 95% CI comparing the prevalence of AR between cases with SLE and controls without SLE. Point estimates and standard errors from each eligible study were combined together using the generic inverse variance method of DerSimonian and Laird. Results: A total of 21 486 articles were retrieved. After 2 rounds of review, 1 cohort study and 7 case-control studies with 3 326 171 participants were included into the meta-analysis. The pooled analysis found that patients with AR had a significantly higher risk of SLE than individuals without AR with the pooled OR of 1.36 (95% CI 1.08-1.72; I2 of 80%). Conclusions: A significantly increased 1.4 fold risk of SLE among patients with AR was observed in this systematic review and meta-analysis.